Information Professionals’ Use of Social Networking Sites in the time of Medical Emergency - Oumair Naeem, Farhana Saeed Hashmi, Ghulam Farid, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To explore the most used Web 2.0 tools for health information during COVID-19, to identify the most used social media tool for health information during COVID-19 and to explore the type of health information explored on social networking sites Method: The present study specifically explored the librarians' approach to using social networking sites for the provision of information services. The present study measured librarians' use of social networking sites to provide health information quantitatively. For this purpose, a structured questionnaire was used to survey librarians of university libraries in Punjab.` Results: The results of the study validated that information professionals are keen and active in using social media for seeking out health information and also rely on more personal networks like WhatsApp. They searched for COVID-19-related information mostly other than fetching out general information. For this reason, we mostly relied on discussion groups, not random information-seeking. This shows their level of committed indulgence in these social media platforms, and they used their information literacy skills to seek health information. Conclusion: University librarians are an essential and vital element of any university, and they should be investigated in order to improve their services and resources to meet the demands of their users and researchers. Keywords: Health Information Seeking; Health resources, Social Networking Site; Covid-19